PENGGUNAAN PROTEASE DALAM PAKAN YANG MENGGUNAKAN LIMBAH PERTANIAN-PETERNAKAN UNTUK MENINGKATKAN KINERJA PERTUMBUHAN AYAM BROILER - Apriliana Devi Anggraini; Ferry Poernama; Chusnul Hanim; Nanung Danar Dono (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
This study was aimed to determine the effects of protease supplementation in diets with agricultural-livestock by products on the growth performance in broiler chickens. The commercial protease used in current study was produced by Bacillus licheniformis which based on keratinase. The treatment diets were a control basal diet without agricultural-livestock by-products and protease supplementation (P1); P1 + 0.05% protease; basal diet with meat bone meal (MBM) and distiller’s dried grain with soluble (DDGS) suppementation (P3); P3 + 0.05% protease (P4); basal diet with hydrolized chicken feather meal (HCFM) and DDGS supplementation (P5); P5 + 0.05% protease. The obtained data were statistically analyzed using Complete Randomized Design, and analyzed subsequently by Orthogonal Contrats Test. Results showed that protease supplementation in the diets containing agricultural-livestock by-products did not affect growth performance of broiler chickens in starter phase and overall age phase. However, in diets containing MBM, protease supplementation reduced the nett gain and feed conversion ratio (FCR) in finisher phase (P<0.05). In diets containing HCFM, protease supplementation increased nett gain and FCR (P<0.05), compared to those of containing MBM. It could be concluded that qualified HCFM, MBM, and DDGS can be used as alternatives for protein-energy source feed stuffs in starter phase, as they did not reduce growth performance of broiler chickens. Protease used in this study might be more effective in diets containing HCFM than those of containing MBM and DDGS.Keywords: Agricultural-livestock by-products, Broilers chickens, Growth performance, Protease.